Relationship Between Family Socioeconomic Status and Learning Burnout of College Students: The Mediating Role of Subjective Well-Being and the Moderating Role of Resilience - Wu, Wenzhi; Liu, Yilin; Yu, Lei; Guo, Zhichao; Li, Shujun; Guo, Zeyi; Cao, Xiang; Tu, Fangjun; Wu, Xiaoqin; Ma, Xiao; Long, Qing; Zhao, Xinling; et al. (Frontiers in Psychology, 2022)
OBJECTIVE Learning burnout affects the positive development of College Students. The present study aimed to investigate the relationship between Family Socioeconomic Status (FSES) and learning burnout, as well as the mediation effect of subjective well-being and the moderation effect of resilience in this relation. METHODS 550 Chinese college students from Yunnan completed a questionnaire measuring the research variables in this study. RESULTS (1) after controlling for participants ‘gender and age, FSES negatively and significantly predicted learning burnout; (2) subjective well-being partially mediated the relationship between FSES and learning burnout; and (3) the direct effect of FSES on learning burnout and the mediation effect of subjective well-being was moderated by resilience. The level of learning burnout of individuals with low resilience increased significantly with the decrease of FSES, and the level of learning burnout of individuals with high resilience decreased significantly with the increase in subjective well-being. CONCLUSION The present findings support the moderated mediation model underlying the relationship between FSES and learning burnout. This also has significant implications for formulating prevention and intervention measures on learning burnout among college students. LIMITATIONS First of all, this study used the cross-sectional study design, which cannot make a causal inference. In addition, the sample in this study is university students from Kunming, which may affect the popularity of the results.